2009
DOI: 10.1007/s11671-009-9303-0
|View full text |Cite
|
Sign up to set email alerts
|

Biological Synthesis of Size-Controlled Cadmium Sulfide Nanoparticles Using ImmobilizedRhodobacter sphaeroides

Abstract: Size-controlled cadmium sulfide nanoparticles were successfully synthesized by immobilizedRhodobacter sphaeroidesin the study. The dynamic process that Cd2+was transported from solution into cell by livingR. sphaeroideswas characterized by transmission electron microscopy (TEM). Culture time, as an important physiological parameter forR. sphaeroidesgrowth, could significantly control the size of cadmium sulfide nanoparticles. TEM demonstrated that the average sizes of spherical cadmium sulfide nanoparticles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 19 publications
5
37
0
Order By: Relevance
“…The positive sample was treated with distilled water, which replaced urea and SDS. The supernatant was concentrated in a Millipore Centricon centrifugal filter unit, and then analyzed by SDS-PAGE to determine presence of proteins (Bai et al 2009a). …”
Section: Protein Characterization By Sds-polyacrylamide Gel Electrophmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive sample was treated with distilled water, which replaced urea and SDS. The supernatant was concentrated in a Millipore Centricon centrifugal filter unit, and then analyzed by SDS-PAGE to determine presence of proteins (Bai et al 2009a). …”
Section: Protein Characterization By Sds-polyacrylamide Gel Electrophmentioning
confidence: 99%
“…It has been found that R. sphaeroides have promising antioxidant and anticancer properties and prolong longevity . We have successfully utilized the photosynthetic bacteria Rhodopseudomonas palustris and Rhodobacter sphaeroides for synthesizing ZnS, PbS, and CdS nanoparticles (Bai and Zhang 2009;Bai et al 2006Bai et al , 2009a. He et al (2007He et al ( , 2008 synthesized gold nanoparticles and nanowires using extracts of Rhodopseudomonas capsulate.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods are challenged by restricted selectivity and large amounts of toxic chemicals involved in the process resulting in secondary pollution . Compared with traditional methods, biological methods have great appeal because of their simplicity, elimination of toxic chemicals (Mishra et al 2014), and capability of controlling nanoparticle size (Bai et al 2009;Sathishkumar et al 2010a). Over the last decade, adsorption and reduction of heavy metals by microorganisms including bacteria, yeast, and fungi have been reported (Farooq et al 2010;Lo et al 2014;Tan et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively fewer works are reported on the green synthesis of metal sulphide semiconductor nanoparticles [15][16][17]. Green syntheses of ZnS nanoparticles have been reported by using microbes (Rhodobacter sphaeroides) [18].…”
Section: Introductionmentioning
confidence: 99%